Success or failure predictive indexes of extubation in renal transplants patients under mechanical ventilation – pilot study - Silva, Luciana Domingues Angelo da; Almeida, Marcella M. Musumeci F.; Quaresma, Matheus Oliveira; Castro, Talita; Santos, Mariana Ares; Chiavegato, Luciana Dias (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Currently, chronic kidney disease (CKD) is a major health problem and in the most severe conditions, kidney transplantation is an alternative treatment. However immunosuppression induced these patients to respiratory complications and endotracheal intubation. In order to assist the decision of the best time for weaning and extubation of these patients, there are predictive indexes that should be considered in preliminary assesment. Objective: To check the capacity of predictive indexes for weaning of mechanical ventilation, rapid shallow breathing index (RSBI), oxygenation rate (PaO2 /FiO2 ) and maximum inspiratory pressure (MIP) in predicting the success or extubation failure in kidney transplant patients. Methods: This study is a prospective cohort carried out with patients aged over 18, under mechanical ventilation for more than 24 hours. The patients were submitted to the Spontaneous Breathing Test, also the assessment of the Rapid Shallow Breathing Index, oxygenation index (PaO2 /FiO2 ), and maximum inspiratory pressure (MIP) and they were observed during 48 hours after to evaluate the success and extubation failure. Results: A total of 106 patients were eligible, and 20 of these were included with mean age of 46.9 ± 3.06 years and 14 of the subjects were male. Three patients showed extubation failure, and needed to have reintubation within the period of 48 hours as considered. Conclusion: The indices to predict weaning of mechanical ventilation, when within the expected normal values, seem to be able to predict extubation, with the exception of MIP that, even in cases of success, showed itself to be at levels lower than the predicted percentage.